EFL Students’ Perceptions on Using Kahoot as a Formative Assessment Tool in Vocabulary Acquisition - Rizki Putri Yunisa Khairani; Rahmah Fithriani (FOSTER: Journal of English Language Teaching, 2025)
Technology advancement has equipped vocabulary acquisition processes within an English learning environment with digital formative assessment tools, such as Kahoot. This research aims to reveal EFL students’ perception in using Kahoot as a formative assessment tool for vocabulary learning. This research employs a qualitative method and the research instruments involve questionnaires and interviews distributed and conducted to the selected participants. A purposive sampling method is applied in this research to select the research participants. The research participants consist of EFL students who are enrolled in an English course and have played Kahoot more than five times. Thematic content analysis is utilized to analyze the collected data. The findings show that most students perceive Kahoot positively. Its game like features timers, scores, and leaderboards can help increase interest, motivation, and focus. Students reported better understanding and improved quiz results. However, a few students found it less effective due to personal learning preferences. Overall, Kahoot is seen as a fun and useful tool to support vocabulary learning and can be applied more widely in English language instruction.